Comparison the Effectiveness between Defective Cough and Yoga Breathing Exercises in Reducing Breathlessness on Tuberculosis Patients at Matahari Room, Dr. M. Yunus Hospital, Bengkulu - Weti Dadang; Nopiawati; Haifa Wahyu; Liza fitrilina; Ledyawati (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: The decrease of vital lung capacity on pulmonary tuberculosis (PTB) patients can reduceoxygen supply to the lungs. Lung capacity is very crucial within breathing process; decreased its capacitycan cause the distruption functions in the body’s cells, which leads to the breathlessness on tuberculosispatients. This research presents the study to examine the Effective Coughing (EC) and Yoga breathingExercises (YBE) as a technique to reduce the breathlessness for patients who suffer from tuberculosis atRegional Public Hospital, DR.M.Yunus, Bengkulu.Methods: This study was quantitative research with a quasy experiments design. The population was allpatients (men and women) with pulmonary tuberculosis (PTB) at RSUD DR.M.Yunus, Bengkulu. Thesamples were 74 patients, which selected toward patients who have complaints of breathlessness; 34 patientsused for intervention group, and 34 patients for control group. This, according to the research’ aim, comparedthe treatment effect by using effective coughing intervention and Yoga Breathing Exercise as well.Findings: The results showed a significant change after given effective cough (EC) (value=2.30), but therewas a small change after given with Yoga Breathing Exercises (YBE) (value=2.84).Conclusions: In short, our research finding there was a significant effect of using EC and YBE for reducingthe breathlessness. The impications of this research can be implemented as respiratory managementintervention on patients who suffer with pulmonary tuberculosis (PTB).